Improved precision of 3-dimensional optical imaging for anthropometric measurement using non-rigid avatar reconstruction and parameterized body model fitting - Tinsley, Grant M.; Harty, Patrick S.; Siedler, Madelin R.; Stratton, Matthew T.; Rodriguez, Christian (Clinical nutrition open science, 2023)
Three-dimensional optical imaging for digital anthropometry and body composition estimation is increasingly available to health professionals and individual consumers. The purpose of the present analysis was to examine the precision of a scanner that employs non-rigid avatar reconstruction and parameterized body model fitting. Sixty-nine healthy adults (37 F, 32 M; [mean ±SD] age: 24.1±5.5 y; height: 169.2±13.9 cm; BMI: 26.0±5.2 kg/m2) were evaluated through duplicate scans using a second-generation prototype three-dimensional optical scanner. Test-retest precision was established using the intraclass correlation coefficient (ICC), root-mean-square coefficient of variation (RMS-%CV), precision error (PE), and least significant change. Across 21 non-ankle body circumferences, PE ranged from 0.4 to 0.8 cm, RMS-%CV ranged from 0.4 to 1.4%, and ICC values were 0.975–0.999. Compared to the first-generation scanner (PE: 0.8–1.0 cm; RMS-%CV: 0.8–1.2%), the errors of waist and hip circumferences were reduced by half (PE: 0.4–0.5 cm, RMS-%CV: 0.4–0.6%). Estimated body fat percentage also demonstrated very high reliability (PE: 0.2%, RMS-%CV: 0.7%, ICC: 0.999). These findings support the improved precision of a second-generation scanner reconstructing a non-rigid avatar subject and parameterized body model fitting and demonstrate the low measurement error that is achievable with this technology.